Examination of an emotion-focused therapy intervention to promote self-forgiveness for interpersonal offenses - Cornish, Marilyn Ann (2014)
This study examined the effectiveness of a newly-developed emotion-focused counseling intervention designed to increase self-forgiveness for regretted actions committed against another person. Twenty-six participants who indicated they had unresolved emotions about a past offense enrolled in the study and were randomly assigned to a delayed or immediate treatment condition. Twenty-one participants completed the study. Results demonstrated the intervention had positive effects on both offense-specific emotional responses and on general well-being. After controlling for screening scores, participants who received the treatment had significantly lower self-condemnation and significantly greater state self-forgiveness and self-reported self-forgiveness than did participants who spent time on a waiting list. Again controlling for screening scores, treated participants also had significantly lower psychological distress and significantly greater self-compassion at the end of treatment than did participants who spent time on a waiting list. Satisfaction with life was only marginally impacted by the intervention relative to the waiting list. Results of this study demonstrate the utility of this new intervention for helping clients resolve the negative residual effects of unforgiveness toward the self